Pengembangan Perangkat Pembelajaran dengan Menggunakan Model Team Based Learning untuk Meningkatkan Hasil Belajar Fisika - Dariani Dariani; Asri Arbie; Muhammad Yusuf (Educatio, 2022)
This research was conducted at SMA Negeri 1 Telaga Biru and aimed to produce quality physics learning tools using the Team-Based Learning (TBL) learning model. The device was developed using the 4D development model developed by Thiagarajan Semel and Semel. The research results on the device show that the developed device is of high quality. Learning tools are said to be valid for use with slight revisions. This can be seen based on the average validation results with a value of 3.5 and 3.6. The level of effectiveness of learning devices is seen in the increase in student learning outcomes consisting of the cognitive domain at the first meeting until the third meeting, N Gain iRat is 0.46 with n criteria of moderate gain, at tRat is N Gain 0.5, in the attitude domain with an average the percentage of 80.240%, the results of observing student activities for 3 meetings are 80.890% with good criteria and the psychomotor aspect an average percentage of 80.128%, and the practicality of the developed device seen from the observation sheet on the implementation of learning 93.650% and the teacher's response questionnaire and student responses with an average percentage of 81.653% and 79.752%. Get a positive response.